Anthropology and Cryptozoology: Exploring Encounters with Mysterious Creatures edited by Samantha Hurn and Chris Wilbert (in the series Multispecies Encounters) - Mayer, Gerhard A. (Journal of Scientific Exploration, 2020)
Show me a Sasquatch body. (Michael Shermer, 2009, p. 35) Anthropology and anatomy professor Jeff Meldrum gave a lecture at the 2016 PA/SSE conference entitled “Sasquatch and Other Wildmen: The Search for Relict Hominoids” (Meldrum, 2016). As one of the few established academics interested in cryptozoological topics, he spoke about footprints of different provenance, their evaluation and anatomical classification. He mentioned the reactions of his colleagues to this field of research and the placement of his books in bookstores for economic reasons—booksellers put them on the esoteric shelves, where sales are expected to be higher for such topics. With reference to the skeptic Michael Shermer, he says the attitude of his colleagues toward the subject area of cryptozoology can be characterized by the sentence “The science starts once you have a body.” This aptly shows the problematic situation in which cryptozoology finds itself. The first sentence of the article “Cryptozoology” in the English Wikipedia asserts: “Cryptozoology is a pseudoscience and subculture that aims to prove the existence of entities from the folklore record, such as Bigfoot, the chupacabra, or Mokele-mbembe.”1 As is often the case with anomalies research, a general judgment is made about the field of research and the people who are actively interested in it. Without a discriminating perspective, critics equate the former with the latter (“pseudoscience and subculture”). The volume Anthropology and Cryptozoology: Exploring Encounters with Mysterious Creatures shows that there are other ways to look at this field. This high-priced book, edited by anthropologist Samantha Hurn, was published in 2017 by the scientific publisher Routledge. The combination of anthropology and cryptozoology in its title shows a shift in academic approach to this topic from zoology and biological anthropology to ethnology and social sciences, evidenced in the book blurb: Cryptozoology is best understood as the study of animals which, in the eyes of Western science, are extinct, unclassified, or unrecognised. In consequence, and in part because of its selective methods and lack of epistemological rigour, cryptozoology is often dismissed as a pseudo-science. However, there is a growing recognition that social science can benefit from engaging with it, for as social scientists are very well aware, ‘scientific’ categorisation and explanation represents just one of myriad systems used by humans to enable them to classify and make sense of the world around them.